ANALISIS PENDAPATAN INDUSTRI RUMAH TANGGA GULA AREN DESA KAAYURAN ATAS KECAMATAN LANGOWAN SELATAN - Mysel Erika Walangitan; Esry Olly Harryani Laoh; Rine ., Kaunang (Sam Ratulangi University, 2021)
This study aims to understand the level of income of the palm sugar home industry in Kaayuran Atas Village, South Langowan District. This study was conducted in February 2021. The data collected in this study is a primary data, which is the data obtained through direct interviews with respondents in the field using a list of questions (questionnaires). And secondary data obtained from agencies related to research problems (related agencies), including physical data of Kaayuran Atas Village and data related to research. The results showed that the income of the palm sugar home industry in Kaayuran Atas Village, South Langowan District, was obtained from the reduction between the average income of the palm sugar home industry of Rp. 5,839,166/month with a production cost of Rp. 5,885,469 then the cost is lacking than Rp. 46,303/month indicates that the palm sugar home industry in Kaayuran Atas Village suffers a loss, but because it uses labor from the family member so that the average labor cost is Rp. 3,600,000 being excluded then the total production cost becomes Rp. 2,209,000 so that the income of the palm sugar household industry in Kaayuran Atas Village is Rp. 3,319,000 making the palm sugar home industry doesnâ€™t suffer from a loss because itÂ exclude the labor costs and they (the palm sugar home industry managers) still have other jobs such as gardening.